An examination of works for wind band: Old churches by Michael Colgrass, Little suite for band by Clare Grundman, This is my father’s world by Franklin L. Sheppard and Hymn setting by Fred J. Allen, and Prelude and primal danse by Ed Huckeby - Jochum, Dara C. (Kansas State University, 2009)
This document is based on the preparation, rehearsal, and performance of selected pieces for the Graduate Conducting Recital of Dara C. Jochum. The pieces examined in the theoretical and historical analysis for this report are Old Churches by Michael Colgrass, Little Suite for Band by Clare Grundman, This Is My Father’s World by Franklin L. Sheppard with hymn setting by Fred J. Allen, and Prelude and Primal Danse by Ed Huckeby. This document also contains rehearsal plans and procedures for the preparation of the literature. The recital was performed on March 7, 2008 in Hart Recital Hall on the campus of the University of Central Missouri, and was performed by the members of the Leeton High School Concert Band as well as guest performers from the University of Central Missouri Wind Ensemble.
Keywords: Wind band; Score analysis; Education, Music (0522)